Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran IPAS Melalui Model Pembelajaran Kooperatif Tipe STAD Berbantuan Media Visual di Kelas IV SDN Inpres Koya - sri rahmawati raoda; Rizal Rizal; Surahman Surahman (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2025)
The main issue addressed in this study is the low learning outcomes of fourth-grade students at SDN Inpres Koya in the science subject, particularly on the topic of force. The researcher implemented the Student Teams Achievement Divisions (STAD) cooperative learning model in science lessons on force for fourth-grade students at SDN Inpres Koya. The STAD cooperative learning model consists of six phases: (1) conveying objectives and motivating students, (2) presenting information, (3) organizing students into learning groups, (4) guiding groups to work and learn, (5) evaluation, and (6) providing rewards. This study employed Classroom Action Research (CAR) and was conducted in two cycles, each consisting of two meetings. The results of Cycle I, which focused on types of forces, indicated that classical student mastery reached 80% with an average score of 72. In the first meeting, teacher activity observation reached 82% and student activity observation reached 86%; in the second meeting, teacher activity observation increased to 86%, while student activity observation was 76%. In Cycle II, teacher activity observation reached 88% and student activity observation reached 91% in the first meeting; in the second meeting, teacher activity observation increased to 94% and student activity observation to 95%. Furthermore, in Cycle II, the percentage of classical student mastery increased to 90%, with an average score of 73. Therefore, it can be concluded that the implementation of the STAD cooperative learning model can improve learning outcomes on the topic of force for fourth-grade students at SDN Inpres Koya.